Tipagem molecular da cápsula de Haemophilus influenzae isolados da nasofaringe de crianças de creches de Goiânia - CARVALHO, Camila Xavier de (2010)
Haemophilus influenzae (Hi) causes infection in children, and is presented in two ways: with six encapsulated serotypes a-f and non-encapsulated or nontypeable (NTHi). Capsulated strains are responsible for a variety of invasive diseases, with meningitis being the most frequent. Nontypeable strains are responsible for respiratory tract infections and acute otitis media in children under 24 months. Children who attend day care centers have increased risk of developing otitis media when colonized with NTHi. Our goal was to describe the prevalence of colonization by Hi and risk factors associated with carrier status in children attending day care centers. Nasopharyngeal swabs collected from 1192 healthy children under five years of age who attended one of 62 daycare centers in Goiânia - Goiás, Brazil were analyzed. The samples were placed on chocolate agar plates and incubated in an atmosphere containing 5% CO2 at 37 ° C overnight. Hi were identified according with colony morphology in culture, Gram staining, and their requirement for V (hemin) and X (NAD) factors. Capsular typing and the presence of the genes TEM1 and ROB1 for resistance to β-lactams were evaluated by PCR. Differences between proportions and means were tested using Chi-square and Student's t test, respectively. Estimates of relative risk (odds ratio) were evaluated by univariate and multivariate logistic regression, p values less than 5% were considered statistically significant. The prevalence of colonization among the 1192 children was 32.1% and 23.3% for HiNT and 8.8% for encapsulated strains. The prevalence of strains carrying the gene TEM1 was 38.4%. Among HiNT strains the prevalence of TEM1 gene was 43.2%. Previous hospitalization of children in the last 6 months was independently associated with the risk carrier by H. influenzae typeable. The data described in this study will aid investigation on the impact of the 10-valent pneumococcal vaccine (PHiD-CV) introduction.